Parent-child communication in sport: Bridging the gap between theory and research - Grimm, Marshall Xavier; Dorrance Hall, Elizabeth; Dunn, Charles Ryan; Dorsch, Travis Edward (Journal of Amateur Sport, 2017)
Parent-child communication is integral to the acquisition of positive developmental outcomes from sport. This position paper offers useful interdisciplinary frameworks and theories for future researchers as they investigate questions pertaining to parentchild communication in organized youth sport. We propose such work is enhanced when grounded in family, human development, and interpersonal communication theory and literature. Specifically, theoretical frameworks from these areas assist researchers in determining salient research questions, choosing appropriate methodologies, and most importantly in the interpretation of findings. As researchers attempt to further understand parental influence in sport, the role of specific family processes like communication will shed light on the potential mechanisms that drive youth’s developmental outcomes. This knowledge will likely lead to better outcomes for youth participating in sport, and better relationships among family members in and out of the sport context. By gaining greater understanding of this phenomenon, researchers will have a more complete set of tools to educate parents, administrators, and coaches in an evidence-based way.